2022
DOI: 10.1111/pai.13776
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in nasal airway epithelium from overweight or obese youth with asthma

Abstract: Background The mechanisms underlying the known link between overweight/obesity and childhood asthma are unclear. We aimed to identify differentially expressed genes and pathways associated with obesity‐related asthma through a transcriptomic analysis of nasal airway epithelium. Methods We compared the whole transcriptome in nasal airway epithelium of youth with overweight or obesity and asthma with that of youth of normal weight and asthma, using RNA sequencing data from a cohort of 235 Puerto Ricans aged 9–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
(99 reference statements)
1
4
0
Order By: Relevance
“…A previous study in A549 cells investigated the overexpression of the Toll-like receptor (TLR), that has an important role in the innate immune system, and observed a decreased expression of among others CXCL10 and CCL20 in the cell supernatant due to the overexpression of TLR10, 88 similar to our findings in cell lysate. Furthermore, a meta-analysis of nasal epithelium from children between 6 and 16 years of age, demonstrated decreased expression of CXCL11 and CXCL10 in patients with obesity-related asthma 89 and is also in line with our hypothesis that the overexpression of CCL26 causes a more severe asthma phenotype, based on previous findings in nasal epithelium. 10 In a study of A549 cells infected with respiratory syncytial virus (RSV), higher concentrations of CXCL10 and CCL3 were identified in the cell supernatant 24 h after RSV infection.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study in A549 cells investigated the overexpression of the Toll-like receptor (TLR), that has an important role in the innate immune system, and observed a decreased expression of among others CXCL10 and CCL20 in the cell supernatant due to the overexpression of TLR10, 88 similar to our findings in cell lysate. Furthermore, a meta-analysis of nasal epithelium from children between 6 and 16 years of age, demonstrated decreased expression of CXCL11 and CXCL10 in patients with obesity-related asthma 89 and is also in line with our hypothesis that the overexpression of CCL26 causes a more severe asthma phenotype, based on previous findings in nasal epithelium. 10 In a study of A549 cells infected with respiratory syncytial virus (RSV), higher concentrations of CXCL10 and CCL3 were identified in the cell supernatant 24 h after RSV infection.…”
Section: Discussionsupporting
confidence: 91%
“…IL-15 has also been shown to promote Th2 differentiation and allergic sensitization in a mouse model of asthma 36 . Finally, induction of SOCS1 by PGAP3 may also be important to asthma as RNA-sequencing analysis of human nasal epithelial cells from children with asthma found significant expression of SOCS1 37 that is known to regulate cytokine signaling in both human bronchial epithelial cells from patients with asthma 38 and in the lungs of a mouse model of asthma 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Different studies of peripheral blood white blood cells (WBCs) have identified epigenetic and transcriptomic changes in pathways related to immune signaling associated with obesity and asthma, lung function, and other related phenotypes (56,57). More recently, we reported a transcriptome-wide association study (TWAS) in nasal epithelium that found pronounced differences between obese children with asthma and their peers of healthy weight, with most genes related to interferon and non-T2 signaling pathways (58).…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%